Supporting parents for in-home capture of problem behaviors of children with developmental disabilities - Nazneen, N.; Rozga, Agata; Romero, Mario; Findley, Addie J.; Call, Nathan A.; Abowd, Gregory D.; Arriaga, Rosa I. (Personal and ubiquitous computing, 2012)
Ubiquitous computing has shown promise in applications for health care in the home. In this paper, we focus on a study of how a particular ubicomp capability, selective archiving, can be used to support behavioral health research and practice. Selective archiving technology, which allows the capture of a window of data prior to and after an event, can enable parents of children with autism and related disabilities to record video clips of events leading up to and following an instance of problem behavior. Behavior analysts later view these video clips to perform a functional assessment. In contrast to the current practice of direct observation, a powerful method to gather data about child problem behaviors but costly in terms of human resources and liable to alter behavior in the subjects, selective archiving is cost effective and has the potential to provide rich data with minimal instructions to the natural environment. To assess the effectiveness of parent data collection through selective archiving in the home, we developed a research tool, CRAFT (Continuous Recording And Flagging Technology) and conducted a study by installing CRAFT in eight households of children with developmental disabilities and severe behavior concerns. The results of this study show the promise and remaining challenges for this technology. We have also shown that careful attention to the design of a ubicomp system for use by other domain specialists or non-technical users is key to moving ubicomp research forward.